Review on the application of physiological and biomechanical measurement methods in driving fatigue detection - Sanjaya, Kadek Heri; Lee, Soomin; Katsuura, Tetsuo (Research Centre for Electrical Power and Mechatronics, Indonesian Istitutes of Sciences, 2016)
Previous studies have identified driving fatigue as the main cause of road traffic accidents, therefore, the aim of this literature review is to explore the characteristics of driving fatigue both physically and mentally as well as to explore the technology available to measure the process of fatigue physiologically. We performed e-searching in the field of fatigue detection methods through keywords tracking. The instruments studied have their own strength and weakness, and some are intrusive while the others are non-intrusive. The accuracy and stability of measurements are also varied between those instruments. In order to create more reliable fatigue detection methods, it is necessary to involve more instruments with an inter-disciplinary approach. Our intention is to make this study as a stepping stone for a more comprehensive in-vehicle real-time man-machine interaction study. Such study will not only be useful to prevent traffic accidents but also to bridge man and machine communication in the vehicle control along with developing newer technology in the field of vehicle automation.